2022
DOI: 10.1128/spectrum.02418-22
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Pathogen Infection Manipulates Soil Health through Root Exudate-Modified Rhizosphere Microbiome

Abstract: Belowground soilborne disease is the main factor limiting sustainable agricultural production and is difficult to manage due to the complexity of the soil environment. Here, we found that aboveground parts of plants infected by foliar pathogens could enhance the secretion of organic acids, sugars, and amino acids in root exudates to suppress soilborne pathogens and enrich beneficial microbes, eventually changing the plant and soil feedback from negative to positive and alleviating belowground soilborne disease. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Therefore, we speculate that there are many allelopathic/autotoxic substances in ginseng root exudates, and their accumulation drives changes in rhizosphere abiotic or biotic characteristics, resulting in plant-soil negative feedback. It is worth noting that the regulation of crops by root exudates seems to involve complex processes that are entirely dependent on the feedback behavior of the plant-soil system ( Luo et al, 2022 ). A deeper understanding of this feedback behavior is necessary for optimum ecological conservation and agricultural development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we speculate that there are many allelopathic/autotoxic substances in ginseng root exudates, and their accumulation drives changes in rhizosphere abiotic or biotic characteristics, resulting in plant-soil negative feedback. It is worth noting that the regulation of crops by root exudates seems to involve complex processes that are entirely dependent on the feedback behavior of the plant-soil system ( Luo et al, 2022 ). A deeper understanding of this feedback behavior is necessary for optimum ecological conservation and agricultural development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhou et al (2023) found that suitable intercropping systems improved the adaptability of intercropped plants (tomato) by using signaling chemicals released by root exudates (potatoonion) to alter recruitment of the rhizosphere microbiota. Luo et al (2022) showed that when the aboveground part of Panax notoginseng was infected by foliar pathogens, it enhanced its secretion of organic acids, sugars, and amino acids in its root exudates, inhibited soil-borne pathogens, enriched beneficial microorganisms, and reduced underground soil-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…5a to f ). It is well known that plants translocate 40 to 60% of photosynthetically fixed carbon into the root zone and release it as root exudates, providing a source of nutrients for rhizobacterial communities ( 62 , 63 ). Increased photosynthetic performance of plants inoculated with K. cowanii HypNH10 and R. variigena HypNH18 suggest that the more photosynthates would be assimilated, and plants will release more exudates to harbor a higher abundance of bioinoculants, providing direct accessory benefits to the associated host plant for nutrient acquisition and phytohormone production and eventually producing higher biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of the rhizosphere microbiome for plant growth, an in-depth understanding of rhizosphere microbiome assembly and its driving factors is key to rhizosphere engineering for sustainable crop production. The composition and structure of the rhizosphere microbial community can be influenced by many factors, including plant domestication, plant genotype, plant development stage, plant compartment, root exudates, soil type, growth conditions, and agricultural practice (Edwards et al, 2015;Chen et al, 2019;Qu et al, 2020;Bai et al, 2022;Guo et al, 2022;Luo et al, 2022). For instance, Peng B. et al reveal the strong effects of drip irrigation on the rhizosphere bacterial community of cotton as compared with traditional flood irrigation, and indicate that drip irrigation under plastic film mulch alters the core bacterial network module and suppresses soil nutrient cycling.…”
Section: Rhizosphere Microbiome Assembly and Its Driving Factorsmentioning
confidence: 99%